2006
DOI: 10.1634/stemcells.2006-0189
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll‐Like Receptors on Human Adipose‐Derived Stromal Cells

Abstract: STEM CELLS 2006;24: 2744 -2752

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
170
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(196 citation statements)
references
References 44 publications
18
170
7
1
Order By: Relevance
“…The pro-inflammation cytokines (IL-1β, IL-1α, and IL-6) and chemokine (IL-8) related to the TLR4-LPS signalling pathway was also up-regulated at the mRNA and/or protein levels in hWJ-MSCs treated with LPS. The pro-inflammatory state shift provoked by LPS in hWJ-MSCs in our study showed a “dull” response compared to the responses observed in hBM-MSCs and hAT-MSCs [23,24,25,27] but showed similar characteristics to hCB-MSCs [26]. These findings suggested that the hMSCs derived from foetal tissue are not sensitive as the MSCs derived from adult tissues to the LPS engagement [2,4,7,25,26].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The pro-inflammation cytokines (IL-1β, IL-1α, and IL-6) and chemokine (IL-8) related to the TLR4-LPS signalling pathway was also up-regulated at the mRNA and/or protein levels in hWJ-MSCs treated with LPS. The pro-inflammatory state shift provoked by LPS in hWJ-MSCs in our study showed a “dull” response compared to the responses observed in hBM-MSCs and hAT-MSCs [23,24,25,27] but showed similar characteristics to hCB-MSCs [26]. These findings suggested that the hMSCs derived from foetal tissue are not sensitive as the MSCs derived from adult tissues to the LPS engagement [2,4,7,25,26].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, no effect on the proliferation and apoptosis of hWJ-MSCs was found. The results illustrated that LPS engagement modulate the biological function and immune immunosuppressive properties of hWJ-MSCs, similar to hBW-MSCs, hAT-MSCs, and hCB-MSCs [23,25,26]. …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations